2015
DOI: 10.1177/0954410015598792
|View full text |Cite
|
Sign up to set email alerts
|

Metamodel-based optimization of the bolted connection of a wing spar considering fatigue resistance

Abstract: In this paper, the optimization considering the constraint of fatigue life was conducted on a bolted connection of a wing spar, after which a series of fatigue tests were carried out to verify the optimized result. The object of the optimization was to minimize the weight of the bolted connection. Meanwhile, a constraint of fatigue life was taken into account. Considering the nonlinear relationship between the fatigue life and the design parameters, experimental design and Kriging model were applied in the opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…It was found that under the same loads, the optimized structure had a 15.7% reduction in the stress peak and a 122% increase in fatigue life [12]. Xia T et al optimized the bolt connection of the wing spar considering life constraints, and the weight of the optimized structure was only 85% of the original design, with the results showing that the optimized structure was the most effective [13]. Munk D J et al applied topology optimization technology to the structural design of aircraft components and designed a light aircraft landing gear [14].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that under the same loads, the optimized structure had a 15.7% reduction in the stress peak and a 122% increase in fatigue life [12]. Xia T et al optimized the bolt connection of the wing spar considering life constraints, and the weight of the optimized structure was only 85% of the original design, with the results showing that the optimized structure was the most effective [13]. Munk D J et al applied topology optimization technology to the structural design of aircraft components and designed a light aircraft landing gear [14].…”
Section: Introductionmentioning
confidence: 99%
“…Munk et al (5) applied topology optimisation to aerospace design problems and designed a light aircraft landing gear. Xia et al (6) applied DOE (design of experiments) and Kriging model in the optimisation to minimise the weight of the bolted connection of a wing bar, and specimen fatigue tests were carried out to evaluate the optimisation process.…”
Section: Introductionmentioning
confidence: 99%
“…the distance between the axis of the drawbar body and center of groove outline cutter D 2 the distance between the axis of drawbar head and center of groove outline cutter D 3 the distance between the axis of the drawbar head and groove outline D 4 the distance between the axis of the drawbar head and center of groove edge D 5 height of groove D 6 the distance between the axis of the drawbar head and gradient starting point D 7 the distance between the axis of the drawbar head and gradient ending point D 8 the initial thickness of web E elastic modulus K cyclic strength coefficient l i lower limit on the dimension σ f fatigue strength coefficient σ m mean stress ε f fatigue ductility coefficient ε ea elastic strain ε pa plastic strain ε a total strain L life repeats of the structure me elastic poisson '…”
mentioning
confidence: 99%
“…A possible solution to address this problem is to replace the computationally expensive simulations model by surrogate models (inexpensive metamodels) to reduce the computational cost. Numerous existing methods for building surrogate models in recent metamodeling literature, the three most prevalent methods have been frequently applied to build a simplified metamodel for engineering simulations code: response surface methodology (RSM), 16 kriging, 16,17 and artificial neural networks (ANN). 18 Each has its advantages and disadvantages, which it is important to know to select a model adapted to the problem to be treated.…”
Section: Introductionmentioning
confidence: 99%